The Stylish Tillich: Jay Bakker and Revolution Church. Issue 3 (2nd July 2016) - Degoes, Plinio
ABSTRACT: Pastor Jay Bakker, son of televangelists Jim and Tammy Faye Bakker, has appeared on a number of television shows and has been written about in various publications. Yet, his views could not be more different than those of his parents. Bakker's books and sermons reflect an affinity for Paul Tillich. This article argues that Bakker is attempting to establish a popular version of Tillich's theology that is accessible to the masses, focusing on millennials and attempting to map the contours of this new version of Christianity.